Anticipated BSDEs driven by a single jump process. Issue 1 (2nd January 2018) - Hu, Lanying; Ren, Yong; Yang, Li
ABSTRACT: In this paper, we discuss a class of anticipated backward stochastic differential equations related to a finite continuous time single jump process. We prove the existence and uniqueness of the adapted solution. Moreover, a comparison theorem for the solutions is also established.